Ear to the Earth: It Started in the Dark - Chadabe, Joel (Circuit)

(untitled) (Les Presses de l’Université de Montréal, 2015)
Ear to the Earth was an idea that grew out of a power failure on the coast of Maine while I was on vacation. Back in New York, and using acoustic ecology as a conceptual basis, I proposed environmental-sound events to colleagues at the Electronic Music Foundation. The first major festival took place in October 2006. Dr. Cynthia Rosenzweig, Senior Research Scientist at the NASA Goddard Space Center and leader of the Climate Impacts Group, pointed out that climate change was a fact. The first festival, which took place at various venues in New York City, included seven concerts, three panels, and seven installations, among them Suspended Sounds, using sounds of extinct, endangered, and threatened species contributed by The Macaulay Library at the Cornell University Lab of Ornithology. The festival, as a program of the Electronic Music Foundation, became an annual event every October in New York until 2013. In November 2012, we recreated it with an enlarged mission as an independent non-profit corporation in New York.